1993
DOI: 10.1590/s0004-282x1993000100019
|View full text |Cite
|
Sign up to set email alerts
|

Lobectomia temporal no infarto cerebral com efeito de massa

Abstract: Cerebral edema secondary to ischemia can threaten life, mainly due to frequent failure of medical management. Imminent herniation of the temporal lobe can be timely detected by clinical signs and CT-scan. Eight patients (4M, 4F; 48-74 years, mean 62) with ischemic stroke and imminent herniation, were surgically decompressed by a standard temporal lobectomy as described by Olivier for temporal lobe epilepsy. Six patients survived, two died and were considered failure of the procedure, probably due to late surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In this series good outcomes were obtained following surgical resection of infarcted brain tissue in 2 patients who would otherwise have succumbed to intracranial hypertension. While no studies were found regarding the use of decompressive surgery in children, many small studies exist which recommend decompressive resection of infarcted tissue [26][27][28] or decompressive craniectomy [22,29,30] in adult patients with intracranial hyperten sion secondary to infarct-related edema. We believe that infarcted brain, as with any other intracranial mass lesion, should be removed in children with medically intractable intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In this series good outcomes were obtained following surgical resection of infarcted brain tissue in 2 patients who would otherwise have succumbed to intracranial hypertension. While no studies were found regarding the use of decompressive surgery in children, many small studies exist which recommend decompressive resection of infarcted tissue [26][27][28] or decompressive craniectomy [22,29,30] in adult patients with intracranial hyperten sion secondary to infarct-related edema. We believe that infarcted brain, as with any other intracranial mass lesion, should be removed in children with medically intractable intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%